Contribution à l’étude diagnostique et dimensionnement d’un réseau d’assainissement (cas de la cité 19 Mars 1962 Commune d'El Oued) - وفاء, شريط; خديجة, قرقازي (University of El-Oued, 2020)
"Summary: In order to improve the performance of the sewage network, to respond to daily human needs and maintain its health, diagnostic studies are necessary to discover, analyze, interpret and then eliminate faults. The main objective of our study is to ensure that wastewater is disposed of at the outlet in ways that are compatible with public health and environmental requirements. This research allowed us to know the actual operation of the sewage network in the study area in order to improve its operation and to consider the subsequent actions on the network (business, management methods, etc.). "":ملخص من أجل تحسين أداء شبكة الصرف التطهير، للاستجابة لاحتياجات الإنسان اليومية والحفاظ على صحته، الدراسات التشخيصية ضرورية لاكتشاف العيوب وتحليلها وتفسيرها ثم القضاء عليها. الهدف الرئيسي من دراستنا هو ضمان التخلص من المياه المستعملة في المخرج بطرق تتوافق مع متطلبات الصحة العامة والبيئة. أتاح لنا هذا البحث معرفة التشغيل الفعلي لشبكة الصرف الصحي في منطقة الدراسة من أجل تحسين التشغيل والنظر في الإجراءات اللاحقة على الشبكة (الأعمال ، طرق الإدارة ، إلخ). "
Conception et diagnostic du système d'AEP et d'Assainissement- مذكرة ماستر تخصص
Keywords: Key words: wastewater, sanitation, network, diagnosis.; الكلمات المفتاحية : المياه المستعملة ، التطهير ، شبكة ، تشخيص.